Konsep Pendidikan Agama pada Zaman Milenial - Dinil Abrar Sulthani (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2020)
This article was written to explain the concept of religious education in the millennial era. The young generations who are in the millennial era experience various life dilemmas. The potential of the younger generation must be directed in order to understand the substance of their responsibilities. This thought article aims to provide an overview of the importance of reminding each other and synergizing with the younger generation. The older generation took the role to leave the next generation strong, strong in science, religious understanding, and skills innovation. Thought writing is described using the literature method with a qualitative descriptive analysis approach. The results of the study show that 1) The younger generation has the opportunity to become superior individuals, 2) The younger generation can maintain the existence of religion in society, 3) The support of the older generation is very important in controlling the activities of the next generation. The conclusion is that there are three educational concepts that can be realized; 1) Learn more diligently, 2) Practice actualizing knowledge, and 3) Useful for many things.